PENGARUH OMZET PENGHASILAN, TARIF PAJAK, SERTA SELF ASSESSMENT SYSTEM TERHADAP KEPATUHAN WAJIB PAJAK USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KOTA TEGAL - Putri Rizqiyah Yuliyanah; Dien Noviany R; Baihaqi Fanani (Multiplier: Jurnal Magister Manajemen, 2018)
The influence of earning turnover, tax rate and self assessment system on taxpayer compliance of SMSe in Tegal City. (Study on tax payers of Micro, Small, and Medium Enterprises registered in KPP Pratama Tegal). Undergraduate Thesis. Tegal: Faculty of Economics and Bussines, Pancasakti University, Tegal. 2018. The purpose of this research is to the influence of income, tax rate, and self assessment system on taxpayer compliance SMEs in Tegal City. The sample in this research are 83 respondents there are is a bussines owners, micro, small, and medium in Tegal City. This research were collected through is quetionnaires. The test Instrument reliability in this research includes, validity test and reliability test. The test of Classic assumption include normality test, multicolinearity test, and heteroscedasticity test. For hypothesis test, we are using multiple linear regression analysis. The results of this research showed that the variable turnover income and self assessment system haveÂ  simultaneously (together) effect on taxpayer compliance SMEs in Tegal City with a significance value of 0.000. Partially on variable earning turnover have effect on compliance taxpayer SMEs in Tegal City with a significance value of 0,000, variable taxe rate have effect on taxpayer compliance SMEs in Tegal City with a significance value of 0,035, and variable self assessment system have effect on taxpayer compliance SMSe in Tegal City with significance value of 0,011.Keywords: Income Turnover, Tax Rate, Self Assessment System, TaxpayerÂ  Compliance